RALF1 peptide triggers biphasic root growth inhibition upstream of auxin biosynthesis - Li, Lanxin; Chen, Huihuang; Alotaibi, Saqer S; Pěnčík, Aleš; Adamowski, Maciek; Novák, Ondřej; Friml, Jiří (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Plant cell growth responds rapidly to various stimuli, adapting architecture to environmental changes. Two major endogenous signals regulating growth are the phytohormone auxin and the secreted peptides rapid alkalinization factors (RALFs). Both trigger very rapid cellular responses and also exert long-term effects [Du et al., Annu. Rev. Plant Biol. 71, 379-402 (2020); Blackburn et al., Plant Physiol. 182, 1657-1666 (2020)]. However, the way, in which these distinct signaling pathways converge to regulate growth, remains unknown. Here, using vertical confocal microscopy combined with a microfluidic chip, we addressed the mechanism of RALF action on growth. We observed correlation between RALF1-induced rapid Arabidopsis thaliana root growth inhibition and apoplast alkalinization during the initial phase of the response, and revealed that RALF1 reversibly inhibits primary root growth through apoplast alkalinization faster than within 1 min. This rapid apoplast alkalinization was the result of RALF1-induced net H+ influx and was mediated by the receptor FERONIA (FER). Furthermore, we investigated the cross-talk between RALF1 and the auxin signaling pathways during root growth regulation. The results showed that RALF-FER signaling triggered auxin signaling with a delay of approximately 1 h by up-regulating auxin biosynthesis, thus contributing to sustained RALF1-induced growth inhibition. This biphasic RALF1 action on growth allows plants to respond rapidly to environmental stimuli and also reprogram growth and development in the long term.
Keywords: auxin; root growth inhibition; kořeny rostlin; RALF1; Indoleacetic Acids; biphasic regulation; Arabidopsis Proteins; peptidové hormony; Peptide Hormones; Gene Expression Regulation, Plant; fosfotransferasy; Phosphotransferases; Plant Roots; cross-talk; kyseliny indoloctové; regulace genové exprese u rostlin; Arabidopsis; proteiny huseníčku